Electrodeposition of Pt-Ni nanoparticles on graphene as an electrocatalyst for oxygen reduction reaction - Li, Siming; Yan, Xuerong; Shi, Meng; Wei, Pengfei; Lu, Haigang; Zhang, Zhiyang; Zhang, Yong; Li, Yawei (Frontiers in Chemistry, 2022)
Owing to its novel properties, such as high electrical conductivity and large specific surface area, graphene has been found as suitable support material for the electrocatalyst design. This work reports the preparation of platinum-nickel alloy nanoparticles (PtNi NPs) electrocatalyst by electrodeposition of PtNi NPs onto graphene support. The obtained PtNi/graphene electrocatalysts were characterized by high resolution transmission electron microscopy (HRTEM), energy-dispersive X-ray microscopy (EDX), X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS) and thermogravimetric analysis (TGA) indicating the controllable morphological and compositional profiles of PtNi NPs on graphene. The electrocatalytic characteristics of PtNi/graphene toward oxygen reduction reaction (ORR) were systematically investigated showing comparable kinetic performance. Moreover, the graphene during electrodeposition process induces carbon vacancies and defects, increasing interaction between nanoparticles and graphene and enhancing electrocatalytic stability by limiting aggregation of the nanoparticles during accelerated stability test. This work opens a promising path for the preparation of graphene-supported alloy electrocatalyst.